2003
DOI: 10.1128/aac.47.6.1824-1831.2003
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Assessment of Linezolid's Clinical Safety and Tolerability: Comparator-Controlled Phase III Studies

Abstract: Linezolid, an oxazolidinone antibiotic, has 100% oral bioavailability and favorable activities against grampositive pathogens including multidrug-resistant staphylococci, enterococci, and pneumococci. Safety assessments were conducted for 2,046 linezolid-treated patients and 2,001 comparator drug-treated patients from seven controlled clinical trials comparing the activities of linezolid and comparator drugs against nosocomial and community-acquired pneumonia, skin and skin structure infections, and methicilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
98
5
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(114 citation statements)
references
References 31 publications
6
98
5
5
Order By: Relevance
“…Peripheral neuropathy occurred in 3 patients; however, all 3 continued the linezolid treatment under careful monitoring. Lactic acidosis and serotonin syndrome, known side effects of linezolid (7,8), were not seen in our study.…”
contrasting
confidence: 37%
“…Peripheral neuropathy occurred in 3 patients; however, all 3 continued the linezolid treatment under careful monitoring. Lactic acidosis and serotonin syndrome, known side effects of linezolid (7,8), were not seen in our study.…”
contrasting
confidence: 37%
“…A key issue with linezolid, however, is toxicity. Although a number of large postmarketing studies have found linezolid toxicity rates to be similar to those of comparator drugs (140,145,285,382), high rates of toxicity have been found for complex patients, and prolonged therapy should be used with caution in these cases (24).…”
Section: Potentially Active Antimicrobials Currently Availablementioning
confidence: 99%
“…During the follow-up in the intensive care unit, supportive treatment was administered, because development of anemia and thrombocytopenia was not initially linked to the drug. The blood counts should be monitored during use of linezolid (17).…”
Section: Discussionmentioning
confidence: 99%